Van Weegen interviewt in het radioprogramma "Het Capitool" Scheerens, Muller van Ast, Zwageling en Van Aalderen
Van Weegen interviewt in het radioprogramma "Het Capitool" Scheerens, Muller van Ast, Zwageling en Van Aalderen.